An analysis of embeddedness in the value creation in interorganisational networks: an illustrative example in Brazil - Gobbo, Simone Cristina de Oliveira; Fusco, José Paulo Alves [UNESP]; Gobbo Júnior, José Alcides [UNESP] (Inderscience Publishers, 2014)
The purpose of this article is to propose a methodological approach to analyse how the positioning of actors in an interorganisational network can influence the elements of value creation. This study fills a gap in the existing literature by exploring the relationship between the positioning of actors and the value creation in a context of interorganisational networks. The case study method was employed and the data was obtained from four companies of an interorganisational network, located in Brazil, which produces earthmoving equipments. The central actor in this network is benefited through access to resources, power and information of the other network actors. The centrality position seems to help this company in the absorption and diffusion of knowledge among the other network actors. The research indicates, that a dense core (through strong ties) and redundancy (for triangulation and knowledge absorption), benefited the following value creation elements: tangible; intangible; services and economic.
Keywords: Embeddedness; Value creation; Interorganisational networks; Brazil